Plant growth promoting bacteria in the endo- and rhizosphere of halophyte Cakile maritima Scop. - Guerrieri, Angela; Racioppo, Angela; Bevilacqua, Antonio; Conversa, Giulia; Giancaspro, Angelica; Speranza, Barbara; Corbo, Maria Rosaria (Frontiers in Plant Science, 2025)
Beneficial bacteria adapted to hypersaline conditions represent a promising biotechnological tool for enhancing crop productivity in salt-affected agricultural systems, particularly as soil salinization constitutes an increasingly critical global challenge impacting extensive cultivated areas. Halotolerant Plant Growth Promoting Bacteria (PGPB) can stimulate plant growth by increasing soil carbon, nitrogen, and mineral availability and uptake. The present study aimed to isolate, characterize, and select potential halotolerant PGPB from Cakile maritima plants collected in two sites located in Margherita di Savoia, in Apulia. This coastal region harbors a unique and taxonomically diverse indigenous microbiota that remains largely unexplored, potentially serving as a valuable reservoir of beneficial microorganisms adapted to high salinity. Microbiological sampling was conducted in triplicate at three phenological stages (seeding, vegetative growth, and anthesis) of the plant’s life cycle in 2023. A total of 180 isolates (150 rhizobacteria and 30 endophytes) were recovered and characterized using morphological, biochemical, and molecular approaches. Halotolerant isolates exhibiting plant growth promoting traits, including phosphate and silicon solubilization, indole acetic acid and siderophore biosynthesis, ammonia production, and drought and salt tolerance, were selected and genotypically identified. The main result was the selection of three promising isolates (assigned to the genera Pantoea and Bacillus) warranting further validation under field conditions.